Simulation-Based Assessment of the Control of a Hybrid ECS Including a Vapor Cycle System - Arnav Pathak; Victor Norrefeldt (Engineering Proceedings)
Within the Clean Sky 2 regional project, a hybrid environmental control system has been conceived that combines the classical bleed air approach with a vapor cycle cooling in the recirculation air. To protect partners’ IP, a functional mock-up (FMU) model of the hybrid ECS was provided describing the system behavior. This model was interfaced with a zonal model of a 100-passenger regional aircraft cabin to investigate comfort and air quality conditions within the cabin. The interfacing reveals that some optimization of the control algorithm is possible for the hybrid ECS, while some operational points already perform as intended. Hence, the coupled simulation approach, at an early design stage, already shows the strengths and weaknesses of the system conception. Recommendations from the simulation study can subsequently be incorporated into the design before a physical demonstrator is produced.